Isolation of Phyllosilicate–Iron Redox Cycling Microorganisms from an Illite–Smectite Rich Hydromorphic Soil - Shelobolina, Evgenya S.; Konishi, Hiromi; Xu, Huifang; Benzine, Jason; Xiong, Mai Yia; Wu, Tao; Blöthe, Marco; Roden, Eric (Frontiers in Microbiology, 2012)
The biogeochemistry of phyllosilicate-Fe redox cycling was studied in a Phalaris arundinacea (Reed Canary Grass) dominated redoximorphic soil from Shovelers Sink, a small glacial depression near Madison, WI. The clay size fraction of Shovelers Sink soil accounts for 16% of the dry weight of the soil, yet contributes 74% of total Fe. The dominant mineral in the clay size fraction is mixed-layer illite-smectite, and in contrast to many other soils and sediments, Fe(III) oxides are present in low abundance. We examined the Fe biogeochemistry of Shovelers Sink soils, estimated the abundance of Fe redox cycling microorganisms, and isolated in pure culture representative phyllosilicate-Fe oxidizing and reducing organisms. The abundance of phyllosilicate-Fe reducing and oxidizing organisms was low compared to culturable aerobic heterotrophs. Both direct isolation and dilution-to-extinction approaches using structural Fe(II) in Bancroft biotite as a Fe(II) source, and O2 as the electron acceptor, resulted in recovery of common rhizosphere organisms including Bradyrhizobium spp and strains of Cupriavidus necator and Ralstonia solanacearum. In addition to oxidizing biotite and soluble Fe(II) with O2, each of these isolates was able to oxidize Fe(II) in reduced NAu-2 smectite with NO3- as the electron acceptor. Oxidized NAu-2 smectite or amorphous Fe(III) oxide served as electron acceptors for enrichment and isolation of Fe(III)- reducing microorganisms, resulting in recovery of a strain related to G. toluenoxydans. The ability of the recovered microorganisms to cycle phyllosilicate Fe was verified in an experiment with native Shovelers Sink clay. This study confirms that Fe in the native Shovelers Sink clay is readily available for microbial redox transformation and can be cycled by the Fe(III)-reducing and Fe(II)-oxidizing microorganisms recovered from the soil.